Considering eighteenth-century prophecy as transformative work - Andrew Crome (Transformative Works and Cultures, 2019)
This article explores premodern prophecy as a form of transformative work with connections to contemporary fan fiction. This link is established in three ways: through the archontic nature of prophecy, through the prophet's self-insertion into the biblical text, and by viewing prophetic groups as textual communities marked by affective links to characters. These links are examined through a case study of two prophets, Richard Brothers (1757–1824) and Joanna Southcott (1750–1814), with the conflict between them reconceptualized as an affectively driven dispute over claims to character ownership. The article suggests that approaches from fan studies can offer useful perspectives for historians (and vice versa) while cautioning against overly arbitrary ahistorical comparisons between modern fandom and premodern groups.